Evaluation of some carotenoids in grapes by reversed-and normal-phase liquid chromatography : A qualitative analysis - Manuela Mendes-Pinto, Maria (2011)
Carotenoids in grapes of three Port winemaking cultivars were investigated. Extracts were obtained with n-hexane/diethyl ether mixtures (0/100; 20/80; 50/50; 100/0) and analyzed by normal and reversed phase HPLC-DAD. Selection and identification of peaks were based on spectroscopic characteristics - ìmax, (%III/II) and k¢ values, leading to 28 probable carotenoids. Using pure standards, it was possible to identify seven compounds previously described (neochrome, neoxanthin, violaxanthin, flavoxanthin, zeaxanthin, lutein, and â-carotene), one more type of neochrome reported here, for the first time, and in addition, two geometrical isomers of lutein and â-carotene were tentatively described. The remaining 17 need to be further identified. High polarity solvent mixtures lead to qualitatively richer chromatograms. Reversed-phase separations allowed the detection of flavoxanthin and the possible geometrical isomer(s) of â-carotene. Under normal phase, zeaxanthin was detected, and neochromes were better separated from neoxanthin. Extraction with 50/50 n-hexane/diethyl ether mixtures and reversed-phase conditions was the best combination for analysis of the carotenoids, known as precursors of compounds with high aroma impact in wines.